Health care utilization in general practice after HPV vaccination-A Danish nationwide register-based cohort study. - Lene Wulff Krogsgaard; Lene Wulff Krogsgaard; Claus Høstrup Vestergaard; Oleguer Plana-Ripoll; Tina Hovgaard Lützen; Mogens Vestergaard; Morten Fenger-Grøn; Bodil Hammer Bech; Dorte Rytter (PLoS ONE)
Objective The Human Papillomavirus (HPV) vaccine has increasingly been suspected of adverse effects in Denmark since 2013. By using consultations with the general practitioner (GP) as an indicator for morbidity, this study aims to examine the association between HPV vaccination and morbidity in girls in the Danish childhood immunization program. Methods The study is a nationwide register-based cohort study. Both the HPV and the Measles, Mumps and Rubella (MMR) vaccines were offered to 12-year-old girls in Denmark in the study period (2008-2015). Therefore, both vaccines were included as exposures to allow differentiation between potential effects. This resulted in four exposure groups: HPV only vaccinated, HPV+MMR vaccinated, MMR only vaccinated, and Non-vaccinated girls. Outcomes were: daytime consultation rates and frequent GP attendance (> 7 annual GP consultations). We estimated consultation rates by negative binomial regressions analysis and frequent GP attendance by logistic regression analysis. Both analyses were stratified on the years 2008-2013 versus 2014. Results The study included 214,240 girls born in 1996-2002. All vaccinated groups consulted the GP more often than the non-vaccinated group, both before and after the vaccination. After the vaccination, an increase in consultations was observed for all three vaccinated groups; most distinct for girls vaccinated in 2014. For girls vaccinated before 2014, we found a slightly higher risk of frequent GP attendance after vaccination in the HPV only group compared to the non-vaccinated group, whereas in 2014, frequent GP attendance was seen for all three vaccinated groups; most substantial for the MMR only vaccinated group. Conclusion In this study, no exclusive increase in health care utilization was detected after HPV vaccination. However, a general difference in the health care utilization pattern was found between vaccinated and non-vaccinated girls, which increased after the time of vaccination, primarily for girls vaccinated after 2013.